Multilevel Bargaining and the Negotiation of a Regional Trade Agreement: A Classroom Simulation. Issue 2 (31st March 2017) - Kerevel, Yann P.; Hultquist, Philip; Edwards, Margaret E.
ABSTRACT: This article introduces a regional trade agreement (RTA) simulation for undergraduate students. The simulation uses a multilevel bargaining framework, in which students can represent not only governments of negotiating countries but also domestic interests. By allowing students to experience international bargaining at different levels, they gain a deeper understanding of controversial international trade processes.